Effects of Megafol on the Olive Cultivar ‘Arbequina’ Grown Under Severe Saline Stress in Terms of Physiological Traits, Oxidative Stress, Antioxidant Defenses, and Cytosolic Ca2+ - Del Buono, Daniele; Regni, Luca; Del Pino, Alberto Marco; Bartucca, Maria Luce; Palmerini, Carlo Alberto; Proietti, Primo (Frontiers in Plant Science, 2021)
Salinity is one of the most impacting abiotic stresses regarding crop productivity and quality. Among the strategies that are attracting attention in the protection of crops from abiotic stresses, there is the use of plant biostimulants. In this study, Megafol (Meg), a commercial plant biostimulant, was tested on olive plants subjected to severe saline stress. Plants treated with salt alone showed substantial reductions in biomass production, leaf net photosynthesis (Pn), leaf transpiration rate (E), stomatal conductance (gs) and relative water content (RWC). In addition, samples stressed with NaCl showed a higher sodium (Na+) content in the leaves, while those stressed with NaCl and biostimulated with Meg increased the potassium (K+) content in the leaves, thus showing a higher K+/Na+ ratio. Salinity caused the accumulation of significant quantities of hydrogen peroxide (H2O2) and malondialdehyde (MDA) due to the decreases in the activity of antioxidant enzymes, namely superoxide dismutase (SOD - EC 1.15.1.1), ascorbate peroxidase (APX - EC 1.11.1.11), guaiacol peroxidase (GPX - EC 1.11.1.9) and catalase (CAT - EC 1.11.1.6). When olive plants under saline stress were biostimulated with Meg, the plants recovered and showed physiological and biochemical traits much improved than salt stressed samples. Finally, Meg exhibited Ca2+-chelating activity in olive pollen grains, which allowed the biostimulant to exert this beneficial effect also by antagonizing the undesirable effects of hydrogen peroxide on Ca2+ metabolism.